Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1055/a-0855-4469
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological treatment of hepatocellular carcinoma with cavoatrial tumor thrombus – case series and literature review

Abstract: Hepatocellular carcinomas (HCC) that extend into the vena cava and the right atrium have a poor prognosis. Surgical approaches including partial hepatectomy and thrombectomy are the most frequently reported treatment options. However, most patients with advanced HCC are not eligible for complex surgical interventions due to reduced liver function, comorbidities, and metastases. At the same time, systemic treatment options of HCC have expanded in recent years. Here, we report 3 cases of patients with advanced H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…They observed that male patients tend to have higher rate of portal vein thrombosis. Portal vein thrombosis is a critical issue that can deteriorate the prognosis of HCC because it can lead to wide dissemination of tumors through the liver and cause a marked deterioration of hepatic function . The incidence of extra‐hepatic metastases has been reported in 19.66% in our studies and occurred mainly to the lungs.…”
Section: Discussionmentioning
confidence: 59%
“…They observed that male patients tend to have higher rate of portal vein thrombosis. Portal vein thrombosis is a critical issue that can deteriorate the prognosis of HCC because it can lead to wide dissemination of tumors through the liver and cause a marked deterioration of hepatic function . The incidence of extra‐hepatic metastases has been reported in 19.66% in our studies and occurred mainly to the lungs.…”
Section: Discussionmentioning
confidence: 59%
“…In conclusion, long-term survival in patients with HCC and RA TT has been mainly managed either by resection of tumor and TT alone [14,15,21,24,29] or, when surgery was not feasible, with other therapeutic approaches (sorafenib, TACE, systemic chemotherapy, ablation) [10,25,28]. However, long-term survival is also possible when nonsurgical therapeutic options are combined, as in our patient.…”
Section: Discussionmentioning
confidence: 80%
“…Hence, this treatment approach is implemented in patients with a general good health condition and in those with symptoms of congestive heart failure. However, the majority of patients with HCC have poor performance status and they are often not considered as surgical candidates [10]. Therefore, other treatment options including TACE, percutaneous microwave ablation, radiation therapy and systemic therapy with multikinase inhibitors, such as sorafenib, or immune checkpoint inhibitors, such as nivolumab, have also been used for these patients ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations